Klinik Pelatihan Peningkatan Kemampuan Literasi Numerasi Siswa Berbasis Teknologi dan Permainan di SD Swasta Luis Betlehem Kecamatan STM Hilir - Melika Silalahi; Rina Pasaribu; Jose Andre; Imelda Imelda (Yayasan Literasi Sains Indonesia, 2023)
Literacy ability can be understood as the ability to analyze information in the form of text, while numeracy ability is understood as the ability to analyze information in the form of numbers. Both of these abilities help improve one's ability to draw conclusions from the information read. The current rapid development of science and technology really helps students to increase literacy-numeracy more quickly if it can be utilized and developed in learning at school. Some of the things that cause low literacy-numeration skills include low interest in reading, reading is only for learning but not to understand the reading, writing is read only without understanding the reading. Therefore, this training clinic provides fun learning in an effort to improve technology- and game-based literacy. Activities carried out: 1) Explanation of numeracy literacy material which aims to provide information and introduction to students what is meant by numeracy literacy. 2) Discussions discuss and solve numeracy literacy questions, 3) play indoors, this activity is a game using numbers or mathematical calculations but while playing, 4) Outdoor play activities are also learning while playing to improve students' numeracy literacy by hone students' mathematical abilities but still while playing, 5) Using technology by giving quizzes through the quiziz application even though students still have to be guided in using cellphones to complete the quizzes given. Based on these activities, student responses were obtained, including 59% of students' interest in reading increased and 58% of students' interest in learning mathematics experienced an increase after participating in clinical activities to improve numeracy literacy skills based on technology and games.